PWE-057 Colon cancer cells induce 3T3-L1 adipocytes de-differentiation through down regulation of PPARG. (June 2019) - Tabuso, Maria; Christian, Mark; Arasaradnam, Ramesh P
Abstract : Introduction: Adipocyte de-differentiation at the tumour invasive front has been demonstrated in breast, ovarian and colon cancers, although signalling mechanisms are not known. Aim of this study was to evaluate the effect of colon cancer cells on adipocyte de-differentiation. Methods: We investigated interactions between HCT 116 colon cancer cells and murine 3T3-L1 mature adipocytes using an in vitro co-culture system. HCT-116 colon cancer cells were co-cultured with 3T3-L1 adipocytes with and without 1 nM Rosiglitazone, a potent peroxisome proliferator-activated receptor gamma (PPARG) agonist that induces adipocyte differentiation, for 72 hours. Functional and morphological modifications were assessed. Fatty acid binding protein 4 (FABP4), a mature adipocyte marker, and PPARG were evaluated by quantitative real-time polymerase chain reaction (qRT-PCR). Lipid accumulation was evaluated with Oil Red O staining. Statistical analysis was performed using Student's t-test with a cut-off of p-value <0.05. Results: 3T3-L1 mature adipocytes in co-culture with HCT-116 colon cancer cells exhibited significant down-regulation of FABP4 (5 fold change, p<0.05) and PPARG (2 fold change, p<0.05). Treatment with Rosiglitazone of 3T3-L1 adipocytes in co-culture with HCT 116 colon cancer cells could not rescue FABP4 expression compared to treated non-cultured adipocytes (5 fold change, P<0.01). Red Oil O staining showed marked delipidation of co-cultured adipocytes, with appearance of fibroblast-like cells. Conclusion: Results have shown significant down regulation of FABP4 and PPARG in 3T3-L1 adipocytes induced by HCT 116 colon cancer cells. Rosiglitazone, a potent PPARG agonist, could not rescue expression of FABP4 in 3T3-L1 co-cultured adipocytes. These results provide evidence of colon cancer cell induced adipocyte de-differentiation through PPARG antagonism, which may have a role in sustaining cancer cell survival and progression.